The Influence of the Role-Playing Method to Improve Speaking Skills in the Merauke Pertiwi Kindergarten Group A - Harahap, Dharma Gyta Sari; Hariani FITRIANTI; Mega SUTEKI; Minuk RIYANA; Yacoba Y. IMBANOP (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
The ability to speak is one aspect of language development that needs to be instilled from an early age. The purpose of this study was to (1) describe the application of role-playing in improving speaking skills in group A children of Pertiwi Merauke Kindergarten (2) describe the improvement of group A children's speaking skills through the application of role-playing in Pertiwi Merauke Kindergarten. This research uses Classroom Action Research. This study used two cycles where each cycle of data analysis used qualitative and quantitative analysis. The research instrument used an observation sheet. The results of this study indicate that the child's speaking ability from cycle I to II has increased.